(untitled) (Research, Society and Development, 2022)
Faced with the COVID-19 pandemic, people’s lifestyles and the configuration of interpersonal relationships have been drastically altered, leading to reflection on coping strategies. With a view to minimizing unfavorable and even unknown sensations such as fear and loneliness, living with a pet provides a sense of hope, bonding and security capable of providing them with an increase in well-being. Quality of Life is a construct that, despite having several definitions, has Subjective Well-Being as an existing parameter for its subjective evaluation, measured through self-report. Thus, the aim of this study was to analyze the quality of life of people who adopted animals during the COVID-19 pandemic in the perception of tutors, as well as to characterize their sociodemographic and economic profile; to investigate the meaning of adopting animals for the adopters and if there was interference in the quality of life of the tutors; identify the positive and negative aspects resulting from the adoption of animals. Data collection took place through 18 semi-structured interviews, recorded in audio, followed by transcription and content analysis. Three categories emerged: “The well-being resulting from the experience of adopting a pet”, “Well-being as a positive balance between positive and negative feelings resulting from the adoption of a pet”, and “Holistic well-being provided for adopting a pet. It is concluded that the adoption of animals in the pandemic was an excellent therapeutic alternative, providing their tutors with an improvement in their well-being, favoring their quality of life.